2012
DOI: 10.1185/03007995.2012.703133
|View full text |Cite
|
Sign up to set email alerts
|

Second-line therapy for non-small cell lung cancer in clinical practice: final results and treatment pathways from the SELECTTION observational study

Abstract: In real-world clinical practice the profiles of patients assigned to erlotinib were distinctly different from those assigned to pemetrexed or docetaxel. The most common reason for treatment discontinuation was progressive disease, reflecting adherence to clinical recommendations. It is difficult to extrapolate these findings to the present, as both clinical practice and the approved indications for NSCLC treatments have evolved substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
12
1
1
Order By: Relevance
“…In the Japanese study, single-agent targeted therapy was the most commonly prescribed second-line treatment [13]. Docetaxel, pemetrexed, and gemcitabine were among the top 3 most frequently used single-agent chemotherapeutics across the studies [1522, 2427]. In Japan gefitinib was the most frequently used second-line single-agent targeted-therapy [13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Japanese study, single-agent targeted therapy was the most commonly prescribed second-line treatment [13]. Docetaxel, pemetrexed, and gemcitabine were among the top 3 most frequently used single-agent chemotherapeutics across the studies [1522, 2427]. In Japan gefitinib was the most frequently used second-line single-agent targeted-therapy [13].…”
Section: Resultsmentioning
confidence: 99%
“…In Japan gefitinib was the most frequently used second-line single-agent targeted-therapy [13]. Outside of Asia, the most frequently used single-agent targeted therapy was erlotinib [1519, 22, 24, 25, 27]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of approximately 150–200 patients per country in the first‐line setting was planned on the basis of precision estimates and attrition rates around the primary objective. Prior real‐world studies have reported that approximately 39% of patients who receive first‐line therapy will receive second‐line therapy (Bischoff et al., 2010; Gerber et al., 2011; Vergnenegre et al., 2012), and 22% of patients who receive second‐line therapy will receive third‐line therapy (Pan, Mallick, Dhanda, & Nadler, 2013). …”
Section: Methodsmentioning
confidence: 99%